Strategi Pemanfaatan Learning Management System berbasis MOODLE untuk Penilaian Pembelajaran di Sekolah Menengah Pertama - Yudhi Kurnia; Dian Hidayati (LP3M, Universitas Muhammadiyah Kendari, 2023)
The Learning Management System (LMS) is an essential system in facilitating learning activities during the Covid-19 pandemic. Therefore, this research aims to identify the strategies employed by teachers in utilizing the Moodle-based LMS. The research methodology adopts a qualitative approach, utilizing online interviews with the system administrators and written communication via WhatsApp with subject teachers. Additionally, a content analysis of the system was conducted by examining the utilized applications. The research findings revealed that the school has implemented several strategies for maximizing the utilization of the Learning Management System. These strategies include: 1) mandating teachers to use the LMS, 2) improving the school's server capacity, and 3) providing training sessions to teachers on system usage.